AWARENESS AND ATTITUDES TOWARDS EMERGENCY CONTRACEPTIVES (EC) AMONG UNDERGRADUATE STUDENTS IN MAKURDI NORTH CENTRAL NIGERIA. - MT, Maanongun; AA, Ornguze; PO, Eka; AO, Ojabo; TZ, Swende; SK, Hembah-Hilekaan (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Objective: The study sought to establish the awareness, utilization and attitude towards the use of EC among female undergraduates. Method: This is a descriptive cross-sectional study that was conducted among 397 female undergraduates of the Benue State University, Makurdi between May and June 2016. Results: Out of the 400 subjects recruited 397(99.3%) were analyzed. Most of them 358(90.2%) were 25 years and below. Majority of them 370(93.2%) were single and 186 (49.6%) were sexually active. Of the sexually active, 51(27.4%) had multiple sexual partners and 63(33.9%) had been pregnant at one time or the other. Overall 172(43.3%) were aware of EC and of these, 103(59.9%) had utilized them. Awareness was highest among those with multiple sexual partners (74.5%) and those who had had a previous pregnancy (68.3%). The most common type of EC used among the respondents was the Levonorgestrel only (postinor 2) pill 88(85.4%). The most common sources of initial information for those who were aware and those who had used EC respectively were peers/friends (37.2% and 44.7%)..Conclusion: Awareness and utilization of EC was low among the undergraduate students. We recommend that efforts should be made to make information about EC and its use available on university campuses.